Legal Protection for E-Commerce Websites Examined from an Intellectual Property Rights Perspective - Yuliani Darmawan; Sapitri Sri Rahayu; Cici Munte; Sri Septiani Dewi (West Science Law and Human Rights, 2026)
Digital transformation in business operations has been driven by the rapid growth of the e-commerce industry in Indonesia. Protecting intellectual property rights (IPR), including copyright, trademarks, and digital information, on e-commerce sites has become increasingly legally challenging due to this trend. This study aims to analyze the legal framework for IPR protection on e-commerce platforms and identify barriers to its implementation. The study uses legislative and conceptual approaches, as well as normative legal research methodology. The findings indicate that although the legal framework for IPR protection has been comprehensively regulated, a lack of awareness among business actors, particularly MSMEs, and an inadequate monitoring and enforcement system have hampered its implementation. To build a fair, safe, and sustainable digital business ecosystem, this study highlights the importance of strengthening law enforcement, improving digital monitoring systems, and enhancing legal knowledge among business actors.